The Oretical Aspects Of Teaching Classical Oriental Languages Based On Digital Technologies - Docent. Ph.D., Bekchonova Shoira Bazarbaevna; Khodjayeva Shakhnozakhan Habibullayevna (Euro Asian Journal Publishing, 2023)
In this article, the teaching of classical oriental languages such as Sanskrit, Arabic, Chinese or Japanese with the help of digital technologies has several theoretical aspects. It is highlighted that the use of digital technologies and their application in educational processes make the education of students more vivid and memorable
Keywords: digital education; educational environment; oriental classical; education